Spatial Regulation of Human Mesenchymal Stem Cell Differentiation in Engineered Osteochondral Constructs: Effects of Pre-Differentiation, Soluble Factors and Medium Perfusion - Grayson, Warren L (2010)
OBJECTIVE: The objective of the study was to investigate the combined effects of three sets of regulatory factors: cell pre-differentiation, soluble factors and medium perfusion on spatial control of human mesenchymal stem cell (hMSC) differentiation into cells forming the cartilaginous and bone regions in engineered osteochondral constructs. DESIGN: Bone-marrow derived hMSCs were expanded in their undifferentiated state (UD) or pre-differentiated (PD) in monolayer culture, seeded into biphasic constructs by interfacing agarose gels and bone scaffolds and cultured for 5 weeks either statically (S) or in a bioreactor (BR) with perfusion of medium through the bone region. Each culture system was operated with medium containing either chondrogenic supplements (C) or a cocktail (Ck) of chondrogenic and osteogenic supplements. RESULTS: The formation of engineered cartilage in the gel region was most enhanced by using undifferentiated cells and chondrogenic medium, whereas the cartilaginous properties were negatively affected by using pre-differentiated cells or the combination of perfusion and cocktail medium. The formation of engineered bone in the porous scaffold region was most enhanced by using pre-differentiated cells, perfusion and cocktail medium. Perfusion also enhanced the integration of bone and cartilage regions. CONCLUSIONS: i. Pre-differentiation of hMSCs before seeding on scaffold was beneficial for bone but not for cartilage formation. ii. The combination of medium perfusion and cocktail medium inhibited chondrogenesis of hMSCs. iii. Perfusion improved the cell and matrix distribution in the bone region and augmented theintegration at the bone-cartilage interface. iv. Osteochondral grafts can be engineered by differentially regulating the culture conditions in the two regions of the scaffold seeded with hMSCs (hydrogel for cartilage, perfused porous scaffold for bone).